Are antimicrobial peptides a double‐edged sword in hidradenitis suppurativa pathophysiology?. (17th November 2021) - Schell, S.L.; Nelson, A.M.
Abstract : Linked Article: Yao et al . Br J Dermatol 2022; 186:236–244 .